Does social capital induce children educational attainment? Evidence from rural community in Terengganu, Malaysia - Abdul Hakim, Roslan; Ismail, Russayani; Abdul Razak, Nor Azam (2010)
The determinants of educational attainment among children have become one of the main research agenda among scholars, educationists and economists alike. In most studies, the focus is on the relationship between educational attainment and factors such as the quality of teachers, schools, educational technologies, curriculum design, the financial and human capital aspect of the families and the ability of children themselves. Recently, the focus has been expanded to explore the relationship between social capital and educational attainment. As an addition to the existing literature, this paper attempts to investigate the impact of social capital on educational attainment using a regression analysis based on a sample of 2500 households, gathered from a rural community in Terengganu, Malaysia. Six domains of social capital are used to arrive at the index of social capital. The argument advanced in this paper is that social capital such as networking, cooperation and trust at the household level is expected to have a positive impact on child's educational attainment.